Expression of DNMTs and H3K9ac in Ameloblastoma and Ameloblastic Carcinoma - Amaral-Silva, Gleyson Kleber do; Morais, Thayná Melo de Lima; Wagner, Vivian Petersen; Martins, Manoela Domingues; Fregnani, Eduardo Rodrigues; Soares, Fernando Augusto; Rocha, André Caroli; Pontes, Helder Rabelo; Santos-Silva, Alan Roger; Vargas, Pablo Agustin (Frontiers in Oral Health, 2021)
Objectives: DNA methyltransferases (DNMTs) and the histone modification H3K9ac are epigenetic markers. This study aimed to describe the immunohistochemical expression of DNMT1, DNMT3A, DNMT3B, and H3K9ac in the dental follicle (DF), ameloblastoma (AME), and ameloblastic carcinoma (AC), correlating these expressions with the recurrence and aggressive behavior in ameloblastoma. Study Design: Immunohistochemical reactions were performed in 10 human DFs, 38 ameloblastomas, and 6 AC samples. Another 59 ameloblastomas assembled in a tissue microarray were used to compare the immunoexpression with the clinical, radiographic, and histopathological characteristics and the presence of BRAFv600e mutation. Each slide was digitized as a high-resolution image and quantified by Aperio ScanScope Nuclear V9 software. All statistical analyzes were performed using GraphPad Prism statistical software. Results: DNMT3B expression was higher in ameloblastomas than in the DFs, while the AC overexpressed all proteins. The ameloblastomas with BRAFv600e mutation, vestibular/lingual, or vestibular/palatine bone cortical disruption and maxilla involvement showed DNMT1 overexpression, while recurrent cases had high DNMT3B levels. Conclusions: DNA methylation and histone modification might play a role in the development, clinical aggressiveness, and recurrence rates of ameloblastoma, such as the progression to AC. Further investigation about gene methylations in ameloblastomas is needed to better understand its relationship with aggressiveness and recurrence.